Nonmotor symptoms in Parkinson’s disease patients in South Asia: A systematic review and meta-analysis - Prayash Paudel; Asutosh Sah (Clinical Parkinsonism & Related Disorders, 2025)
Background: The most common movement disorder and neurodegenerative disorder that progresses over time, Parkinson’s disease, has both motor and nonmotor symptoms. Asia is home to half of the world’s elderly population, and Parkinson’s disease is a common condition in this demographic. Objectives: We aimed to estimate the pooled prevalence of nonmotor symptoms among Parkinson’s disease patients in South Asia based on the available literature. Methods: The study protocol was registered on PROSPERO with reference number CRD42024579956. Databases were searched for observational studies from 2000 to 2024 in English that have assessed the prevalence of nonmotor symptoms among Parkinson’s disease patients in South Asia via validated tools. High-quality studies were included after quality assessment. A random-effects model was used to calculate the pooled prevalence with a 95 % confidence interval. Results: Among the 50 articles (4931 participants) included in the review, 9 (862 participants) used the Nonmotor Symptoms Questionnaire, 9 (803 participants) used the Nonmotor Symptoms Scale, 2 (171 participants) used both, and the remaining 30 (3095 participants) used other validated tools to assess nonmotor symptoms in South Asian patients with Parkinson’s disease. The prevalence of nonmotor symptoms was high, with nocturia being the most prevalent. Psychological symptoms were frequently explained via other tools. Conclusions: Our research is among the few clinical accounts in the literature of the prevalence of nonmotor stmptoms in South Asian Parkinson’s disease patients. Although the heterogeneity of the results could not be fully explained, our study could significantly enhance the understanding of symptoms, leading to more tailored therapeutic and diagnostic strategies.